1977
DOI: 10.1111/j.1365-246x.1977.tb01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Curie depth determination from aeromagnetic spectra

Abstract: We study aeromagnetic maps from four areas in the Western United States: Utah High Plateaus, Yellowstone National Park, Southern Great Basin, and Uinta Basin. In the first area we try to infer depth-to-bottom of magnetic source by comparison of individual anomalies with theoretical fields of vertical prisms. We conclude that this task is impossible, at least for the few anomalies considered. Assuming a bottomless prism a fit can be obtained which is not significantly worse than the best fit obtainable with any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
5

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(78 citation statements)
references
References 24 publications
(19 reference statements)
0
73
0
5
Order By: Relevance
“…Each block covers a square area of 200 km × 200 km. Since magnetic source bodies having bases deeper than window length/2π may not be properly resolved by the spectral method (Shuey et al, 1977), a window length of 200 km is found to be suitable in this study. …”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Each block covers a square area of 200 km × 200 km. Since magnetic source bodies having bases deeper than window length/2π may not be properly resolved by the spectral method (Shuey et al, 1977), a window length of 200 km is found to be suitable in this study. …”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…Calculations of DBMS, which is commonly construed as the Curie-point depth, are made using diverse methods (Spector and Grant, 1970;Shuey et al, 1977;Leu, 1975, 1977;Okubo et al, 1985;Tanaka et al, 1999;Maus and Dimri, 1996;Finn and Ravat, 2004;Ravat et al, 2007;Bansal et al, 2013), namely the spectral-peak method (Spector and Grant, 1970;Shuey et al, 1977), the centroid method Leu, 1975, 1977;Okubo et al, 1985;Tanaka et al, 1999), the scaling spectral or power-law correction method (Maus and Dimri, 1996), forward modelling of the spectral-peak method (Finn and Ravat, 2004;Ravat et al, 2007), and the modified-centroid fractal method Nwankwo, 2015), among others. The conventional centroid method is used in this work for the reason that it gives better estimates with fewer depth errors compared to earlier methods (Ravat et al, 2007).…”
Section: Calculation Of Curie-point Depth Geothermal Gradient and Hmentioning
confidence: 99%
“…Shuey et al (1977) demonstrated that the depth information from the power spectrum can only reach a depth of L/2π. To calculate Zo, Tanaka et al (1999) divided their area of study into several sub-regions of 2 × 2 degrees in size.…”
Section: Depths Of the Top Of Magnetic Sources (Zt)mentioning
confidence: 99%
“…Curie isotherm depth, relation of Curie isotherm depth to Moho depth and source of magnetization within the crust (Shuey et al, 1973(Shuey et al, , 1977Hall, 1974Hall, , 1968Byerly and Stolt, 1977;Krutikovskaya and Pashkevich, 1977;Green, 1976;Smith et al, 1977). The Curie isotherm depth has in the past been considered the position of the Fe 304 Curie point (580o C) isotherm whose depth may vary from S 20 km (Basin and Range) to s 70 km (Sierra Nevada) depending on the geothermal gradient.…”
Section: Recent Interpretations Of Long Wavelength Anomalies Considermentioning
confidence: 99%